Molecular Docking Senyawa α-mangostin sebagai Antiinflamasi secara In Silico - Setyawati, Ni Kadek Ayu Arik; I Wayan Martadi Santika; Putu Sana Yustiantara (Jurnal Jejaring Matematika dan Sains, 2022)
Inflammation is the body's physiological response to infection and tissue injury. Inflammatory mediators, especially cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6) are cytokines involved in acute inflammation. Inflammation can occur when these inflammatory mediators interact with each other. α-mangostin is one of the xanthone that found in the pericarp of mangosteen which has anti-inflammatory activity. The aim of this study was to determine the mechanism of inhibition of ICE protein by α-mangostin in silico with molecular docking. Molecular docking in silico was carried out in several stages, such as preparation and optimization of the 3D structure of α-mangostin, preparation of the target protein, validation of the molecular docking method, and docking of α-mangostin compounds on ICE which refers to the parameters of the bond energy and the type of bond formed. If the bond energy value between the test compound and the target protein is lower, the bonds formed will be stronger and more stable. The results of molecular docking of α-mangostin to ICE protein is the between α-mangostin to ICE protein with a binding energy is about -4,29 kkal/mol. The negative binding energy indicates that α-mangostin has anti-inflammatory activity with an ICE inhibitory mechanism.